Entropia de cadeias polidispersas na rede quadrada - Barros, Pedro Victor Renault de (2011)
The transfer matrix technique is used to calculate the configurational entropy of finite polydisperse chains on the square lattice. Chains are modeled by self-avoiding walks, with excluded volume interactions only and the lattice may be totally or partially covered. Polidispersivity is included by attributing different activities to extreme and internal monomers. These parameters are regulated so that the mean number of monomers per chain is kept finite and therefore no polymerization transition is observed. We build the transfer matrix for strips of finite width and the values of entropy obtained in these strips are then extrapolated to the bidimensional limit, wich corresponds to infinite width.